2018
DOI: 10.3390/w10091135
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Modeling of Climate Change Impacts in a Tropical River Basin: A Case Study of the Cauto River, Cuba

Abstract: The soil and water assessment tool (SWAT) model was applied for the first time in Cuba to assess the potential impacts of climate change on water availability in the Cauto River basin. The model was calibrated (and validated) for the 2001–2006 (2007–2010) period at a monthly timescale in two subbasins La Fuente and Las Coloradas, representative of middle and upper sections of the Cauto basin; the calibrated models showed good performance. The output available for the regional climate Model RegCM4.3 was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 62 publications
(87 reference statements)
1
8
0
Order By: Relevance
“…In the Caribbean region, Cuba showed that under the RCP 8.5 the availability of surface and groundwater in the near future relative to the baseline period is expected to be reduced, with the largest decreases expected during the rainy season (May to October) (Montecelos-Zamora et al, 2018). In this present study, the same pattern of the estimated reduction of water resources was noted, but the largest decrease is expected during the dry season, that is, January to May.…”
Section: Years (Total)supporting
confidence: 75%
“…In the Caribbean region, Cuba showed that under the RCP 8.5 the availability of surface and groundwater in the near future relative to the baseline period is expected to be reduced, with the largest decreases expected during the rainy season (May to October) (Montecelos-Zamora et al, 2018). In this present study, the same pattern of the estimated reduction of water resources was noted, but the largest decrease is expected during the dry season, that is, January to May.…”
Section: Years (Total)supporting
confidence: 75%
“…For our study area, there was not a known set of parameters. Therefore, based on research using SWAT from Jamaica [33], Cuba [34], Brazil [35], Hawaii [36], Portugal [15] and China [32], 16 parameters related to runoff were selected for reservoir inflow (Table 1). To evaluate the significance of the relative sensitivity, the t-stat and p-value were utilized.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Since its release in the early 1990s, SWAT has been extensively used to assess multiple aspects of water resource management in river basins, such as non-point source pollution, land cover/land use changes, soil erosion, alternative management practices and climate change ( [32] and references therein). However, examples from tropical America are limited (e.g., [33,34]). Our model selection was based on considerations such as its ability to represent the physical processes associated with water movement, support documentation and additional software for model calibration and scenario simulation.…”
Section: Hydrologic Modelmentioning
confidence: 99%